HUBUNGAN EFIKASI DIRI DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR IPAS SISWA KELAS TINGGI SDS TORSINA II SINGKAWANG - Aswa; Abd. Basith, Haris Rosdianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is 1) to analyze the relationship between self-efficacy and IPAS learning achievement of high-achieving students, and 2) the relationship between learning motivation and IPAS learning achievement of high-achieving students. This research uses a quantitative approach with a correlational research design. The population in this study consists of upper-grade students from classes IV, V, and VI, with a sample size of 109 students. The research instruments related to students' self-efficacy and motivation in IPAS learning were questionnaires, and learning achievement was taken from students' mid-term exam scores for the even semester of the 2024/2025 academic year. As for the data analysis techniques in this study, Kolmogorov-Smirnov, Pearson product-moment correlation, and Spearman's rank correlation were used. Based on the results of the hypothesis test, it can be concluded that: 1) There is a positive and non-significant relationship between self-efficacy and IPAS learning achievement of high-grade students at SDS Torsina II Singkawang, 2) There is a positive and significant relationship between learning motivation and IPAS learning achievement of high-grade students. Keywords: Self-Efficacy, Learning Motivation, IPAS Learning Achievement